Regulation of entheseal IL-23 expression by IL-4 and IL-13 as an explanation for arthropathy development under dupilumab therapy. (30th November 2020) - Bridgewood, Charlie; Sharif, Kassem; Freeston, Jane; Saleem, Benazir; Russell, Tobias; Watad, Abdulla; Khan, Almas; Loughenbury, Peter; Rao, Abhay; Wittmann, Miriam; McGonagle, Dennis
Abstract: Objectives: Dupilumab blocks the IL-4 receptor (IL-4R) and thus signalling of the 'Th2' cytokines IL-4 and IL-13. It has a license to treat atopic eczema and was recently linked to emergent enthesitis and psoriasis. We investigated the cellular and functional basis for how IL-4/IL-13 regulates the IL-23–IL-17 axis in entheseal stromal, myeloid and lymphocyte cells. Methods: Immunohistochemistry was performed on healthy enthesis samples from patients undergoing elective spinal surgery to investigate entheseal tissue IL-4R expression and cytokine expression by intracellular flow cytometry for IL-4 and IL-13. Digested human enthesis samples were stimulated with lipopolysaccharide (LPS) for IL-23 induction, either alone or with IL-4 or IL-13. Enthesis fibroblasts were stimulated with TNF and IL-17 with and without IL-4 or IL-13 to assess the effect on CCL20 secretion. Synovial fluid samples from PsA patients were also analysed by ELISA for levels of IL-4 and IL-13. Results: The IL-4/IL-13 receptor was present in both the peri-entheseal bone and enthesis soft tissue, and entheseal-derived T cells produced basal levels of IL-4, but not IL-13. Both IL-4 and IL-13 attenuated LPS-induced entheseal IL-23 production. IL-4 also downregulated secretion of TNF/IL-17A-induced CCL20 from entheseal fibroblasts. Both IL-13 and IL-4 were also detectable in the synovial fluid of PsA patients. We also noted a seronegative inflammatory oligoarthritis whilst under dupilumab therapy. Conclusion: Our findings suggest a previously unknown protective role for IL-4/IL-13 in entheseal induction of the IL-23–IL-17 axis. These findings point towards a novel explanation for IL-13 pathway single nucleotide polymorphisms in PsA and also a molecular explanation for why anti-IL-4/IL-13 therapy may induce musculoskeletal entheseal pathology as recently reported.